Stranger than fanfiction - Colfer, Chris, 1990- (New York ; Boston : Little, Brown and Company, 2017)
Four friends embarking on a pre-college road trip from Illinois to California are surprised when Cash Carter, the lead actor from their favorite television show, accepts their invitation to accompany them, and their shared adventure becomes an opportunity to reveal secrets and support each other.
SHS
In English
Keywords: Automobile travel -- Fiction; Secrets -- Fiction; Actors and actresses -- Fiction; Fame -- Fiction; Transgender people -- Fiction; Gay people -- Fiction; Friendship -- Fiction